Etiological analysis of presumed perinatal stroke - (:unkn) unknown (ELSEVIER SCIENCE BV, 2012)
This study aimed to investigate the maternal, pre- and perinatal, and prothrombotic factors with congenital hemiparesis due to presumed perinatal stroke (PPS). Prothrombotic risk factors including protein C and S, antithrombin III, lipoprotein (a), homocystein, factor VIII levels; anticardiolipin antibodies and lupus anticoagulant; methylenetetrahydrofolate reductase mutations, factor V Leiden, prothrombin G20210A mutations were investigated. Arterial ischemic stroke was detected in 60% and periventricular venous infarction in 40%. At least one prothrombotic risk factor was present in 69%, two in 17%, and three or more in 8.5% of cases. The most common combination was methylenetetrahydrofolate reductase C677T and factor V Leiden heterozygosity. The etiology and pathogenesis of PPS is still unclear. According to this study, most of the patients with PPS might have one or more prothrombotic risk factors and certain prenatal risk factors including intrauterine growth retardation, twin gestation and preeclampsia might be related to PPS. (C) 2011 The Japanese Society of Child Neurology. Published by Elsevier B.V. All rights reserved.
Keywords: ARTERIAL ISCHEMIC-STROKE; PROTHROMBOTIC RISK-FACTORS; MATERNAL ANTICARDIOLIPIN ANTIBODIES; CEREBRAL SINOVENOUS THROMBOSIS; 20210 G-A; INHERITED THROMBOPHILIA; NEUROLOGICAL DISORDERS; NATIONAL INSTITUTE; CHILDREN; POPULATION